Passing on and putting to rest: Understanding bereavement in the context of interactive technologies - Odom, Will; Harper, Richard; Sellen, Abigail; Kirk, Dave; Banks, Richard (Proceedings of CHI 2010, 2010)
While it can be a delicate and emotionally-laden topic, new technological trends compel us to confront a range of problems and issues about death and bereavement. This area presents complex challenges and the associated literature is extensive. In this paper we offer a way of slicing through several perspectives in the social sciences to see clearly a set of salient issues related to bereavement. Following this, we present a theoretical lens to provide a way of conceptualizing how the HCI community could begin to approach such issues. We then report field evidence from 11 in-depth interviews conducted with bereaved participants and apply the proposed lens to unpack key emergent problems and tensions. We conclude with a discussion on how the HCI design space might be sensitized to better support the social processes that unfold when bereavement occurs.
Honourable Mention, Best of CHI Award